PCA: THE DETECTION OF INTUITIVENESS - MR. VRISHABH J. SHAH; MR. SHAILESH S. PENKAR; MRS. DEEPA MANOJ (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The study of science brain continually receives information which it processes, evaluates, and compare to the stored information and makes appropriate decisions. This technology serves to detect information in the brain using P300 mermer algorithm along with pattern classification algorithm as a means of detecting the attention, information processing, and memory-related responses to these presentations as revealed by brain waves with the help of biological neural network.